OP0075 Impact of Different Infliximab Dose Regimens on Treatment Response and Drug Survival in 462 Patients with PSA. Results from the Nationwide Registries Danbio and Icebio. (10th June 2014) - Glintborg, B.; Gudbjornsson, B.; Krogh, N.S.; Omerovic, E.; Manilo, N.; Holland-Fischer, M.; Lindegaard, H.; Loft, A.G.; Nordin, H.; Johnsen, L.; Oeftiger, S.F.; Hansen, A.; et al.
Abstract : Background: International guidelines recommend that in psoriatic arthritis (PsA) infliximab should be dosed with 5 mg/kg bodyweight every 8th week. Data on the use of lower doses is however scarce. Objectives: We aimed to describe dose regimens, dose escalation and clinical outcomes in tumor necrosis factor alpha-(TNFi)-naïve patients with PsA treated with infliximab in routine rheumatology care. Methods: Observational cohort study based on the nationwide DANBIO and ICEBIO registries. Stratified by country, characteristics of patients treated with ≤3 mg infliximab/kg body weight, 3-5 mg/kg or ≥5 mg/kg/≈8 wks were described. Outcomes were evaluated by ACR20/50/70 and EULAR-good-response after 6 months, disease activity after 12 months, Kaplan-Meier plots and regression analyses. Results: 462 patients (376 Danish, 86 Icelandic) received treatment with infliximab. In Danish patients, start dose was ≤3mg/kg in 110 patients (29%), 3-5 mg/kg in 157 (42%), ≥5mg/kg in 38 (10%) and unregistered in 71 (19%). In Icelandic patients, corresponding numbers were 64 (74%), 17 (27%), 0 (0%) and 5 (6%). Patients with higher body weight received lower doses per kg. Danish patients received higher doses than Icelandic at baseline (median (IQR) 3.1 (3.0-3.8) mg/kg vs. 2.3 (2.1-2.9) mg/kg, p<0.05) and after 12 months (3.3 (3.0-4.5) mg/kg vs. 2.9 (2.2-3.5) mg/kg, p<0.0001). After 12 months, 58% of Danish and 66% of Icelandic patients maintained treatment. Danish patients had shorter drug survival than Icelandic (1183 vs. 483 days). In univariate analyses stratified by country, time until dose escalation, response rates, drug survival (Figure) and one-year's disease activity were independent of start dose. Drug survival was shorter among patients not receiving concomitant methotrexate. Conclusions: In clinical practice, >70% of Icelandic and Danish PsA patients treated with infliximab received sustained doses below the 5mg/kg/8wks recommended in international guidelines. Lower start doses did not affect drug survival or response. Disclosure of Interest: B. Glintborg: None declared, B. Gudbjornsson: None declared, N. Krogh: None declared, E. Omerovic: None declared, N. Manilo: None declared, M. Holland-Fischer Consultant for: UCB, MSD, Roche, Speakers bureau: UCB, MSD, Roche, H. Lindegaard Consultant for: Lilly, MSD, Nordpharma, Roche, A. G. Loft Speakers bureau: MSD, H. Nordin: None declared, L. Johnsen: None declared, S. Oeftiger: None declared, A. Hansen Speakers bureau: UCB, ABBVIE og MSD, C. Rasmussen Grant/research support: Pfizer, Abbvie, Vertex, Speakers bureau: Pfizer, Abbvie, G. Grondal: None declared, A. Geirsson: None declared, M. Hetland: None declared DOI: 10.1136/annrheumdis-2014-eular.1428